On the problem of the system-integral organizing a dramatic work (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
System analysis explores the formal criteria of literary works, showing the interaction between the elements of the system. Content's factors that make up a high level of artistic literary work, providing artistry only if it’s most comprehensive formal expression. The purpose of this article is to define the concept of system-integrated organization dramatic work. System analysis of a literary work searches factor of forming system and proves the system through the study of literary works between all elements together and bring them regarding the functionality of the main creative units (factor of forming system). On the example of dramatic works of Ivan Tobilevych we trace how all the elements in play organized in system. The results serve as a basis for the study of Ivan Tobilevych’s drama in terms of system analysis. Analysis of system-integrated organization of Tobilevych's drama is extremely important area of research.
Keywords: system; systems analysis; integrity; optimal organization; factor of forming of the system; Ivan Tobilevych